Liver involvement in tuberous sclerosis - Kechaou, Ines (BMJ Publishing Group, 2014)
Tuberous sclerosis complex (TSC) is a rare inherited disease that affects many organs and tissues, which explains the diversity of its clinical manifestations. This disease is often diagnosed at an early age when cutaneous angiofibromas, epilepsy and mental retardation are associated. The hepatic involvement in this phakomatosis is an uncommon location. In this context, we report the case of a tuberous sclerosis revealed in adulthood by abdominal pain and distension related to renal and hepatic angiomyolipomas associated with typical skin lesions.